Geology of Tapanti Quadrangle (1:50 000), Costa Rica - Sojo, Dennis (2017)
We present a geologic map of the Tapantí quadrangle, which is located in the central region of Costa Rica and belongs to the Central Costa Rica Deformed Belt (CCRDB). The CCRDB is a consequence of the interaction of the Cocos Ridge and the Western edge of the Panama microplate. The oldest rocks mapped in this work are Miocene in age and theyvbelongs to Pacacua, Peña Negra and Coris formations, than form the western edge of the Candelaria basin. Three igneous events were distinguished. First, the Miocene volcanic arc, which is represted by the rocks of La Cruz Formation and the clasts of Pacacua Formation. Another period of igneous activity was recorded in Grifo Alto and Doán formations and the Tapantí Intrusive, with an age range of 0.6-0.03 Ma. From a geochemical point of view is remarkable a change between 10 to 6 Ma, enrichment of K and Si and changes in U, Sr, Ba and La concentrations. This change corresponds with the Cocos Ridge arriving to the Middle America Trench and it is visible because the Pliocene magmatic arc, the Pliocene intrusive of Tapantí and the nowadays volcanic arc. The structural model suggests the existence of two deformation events, the first occurred during the period of time between Late Miocene and Pliocene and it formed the Folding Zone Orosi-Patarrá, and the second one corresponds to the establishment of CCRDB, from Pliocene to present, which is constituted by left lateral faults bearing ENE and right lateral faults bearing NW.